Growth Characteristics and Condition Factors Of Red Snapper (Lutjanus campechanus) Landed at PPI Cikidang Pangandaran West Java - Vika Nurlita; Dyahruri Sanjayasari (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Pangandaran waters is one of productive fishing ground for Indonesian fisheries. One of potential catch in this area is red snapper. Red snapper (Lutjanus campechanus) is a type of demersal fish. This species can live in shallow waters to deep seas. Growth measurement is carried out as an anticipation on the presence of overfishing which causes red snapper stocks to decline. Hence, current field work focused on the growth characteristics and factor conditions of red snapper which landed in PPI Cikidang Pangandaran west Java. Present study may provide information related on fish species production. The survey and observation methods were used to collect the data in February 2021. The sampling location was carried out at the PPI Cikidang, Pangandaran. The data of weight and length of red snapper landed at PPI Cikidang were recorded and analyzed descriptively. The results revealed that growth of red snapper landed at the PPI Cikidang was categorized as negative allometric with b < 3, at 1.92. The condition factor has an average of 1.29 which means that the fish are classified as fat or not flat. Keywords: Growth Characteristics; Condition Factor; Red Snapper; Lutjanus campechanus; PPI Cikidang.